Anti–Methicillin-Resistant Staphylococcus aureus Nanoantibiotics - Labruère, Raphaël; Sona, A. J.; Turos, Edward (Frontiers in Pharmacology, 2019)
Nanoparticle-based antibiotic constructs have become a popular area of investigation in the biomedical sciences. Much of this work has pertained to human diseases, largely in the cancer therapy arena. However, considerable research has also been devoted to the nanochemistry for controlling infectious diseases. Among these are due to bacterial infections, which can cause serious illnesses including death. The onset of multi-drug resistant (MDR) infections such as those caused by the human pathogen Staphylococcus aureus has created a dearth of problems such as surgical complications, persistent infections, and lack of available treatments. In this article we set out to review the primary literature on the design and development of new nanoparticle materials for the potential treatment of S. aureus infections, and areas that could be further expanded upon to make nanoparticle antibiotics a mainstay in clinical settings.